2000
DOI: 10.1159/000012161
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Investigation on Pulmonary Metastasis of Head and Neck Carcinomas

Abstract: Objective: To establish a treatment strategy for pulmonary metastases, we clinically investigated the characteristics of distant metastases from head and neck carcinomas. Methods: In 636 head and neck carcinomas, the pathophysiology of distant metastases was investigated by charts, roentgenographies, computed tomographies and scintigraphies. Results: Of the squamous cell carcinomas, oropharyngeal tumors were most highly metastatic, followed by lower gingiva, floor of the mouth, maxillary sinus, and tongue. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Distant metastases from head and neck squamous cell carcinoma involve the lungs most frequently. 16 Screening for pulmonary metastases with computed tomography (CT) scanning, targeted at the high risk population, de ned by tumour stage and histological cell type, has been recommended. 15 Extracapsular spread and positive cervical lymph nodes have also been recognized to be associated with a high (40 per cent) risk of distant metastases.…”
Section: -12mentioning
confidence: 99%
“…Distant metastases from head and neck squamous cell carcinoma involve the lungs most frequently. 16 Screening for pulmonary metastases with computed tomography (CT) scanning, targeted at the high risk population, de ned by tumour stage and histological cell type, has been recommended. 15 Extracapsular spread and positive cervical lymph nodes have also been recognized to be associated with a high (40 per cent) risk of distant metastases.…”
Section: -12mentioning
confidence: 99%
“…A previous study showed that the rate of distant metastasis from the tongue was 4.1%, and was lower than that from upper gingiva carcinomas (6.6%). [ 113 ] The lip cancer comprises 30% of the oral cancer and 2.06% of all cancer cases. [ 114 115 ] The lip carcinoma shows regional lymph node metastasis in 3–29% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, its importance is increasing as loco-regional control improves. Blood borne spread most often involves lung 75,76 . The best predictor of the likelihood of spread is involvement of the neck at multiple levels.…”
Section: Tumor Spreadmentioning
confidence: 99%